Protective effect of ginsenosides Rk3 and Rh4 on cisplatin-induced acute kidney injury in vitro and in vivo - Baek, Seung-Hoon; Shin, Byong-kyu; Kim, Nam Jae; Chang, Sun-Young; Park, Jeong Hill (Journal of ginseng research, 2017)
Nephrotoxicity is the major side effect in cisplatin chemotherapy. Previously, we reported that the ginsenosides Rk3 and Rh4 reduced cisplatin toxicity on porcine renal proximal epithelial tubular cells (LLC-PK1). Here, we aimed to evaluate the protective effect of ginsenosides Rk3 and Rh4 on kidney function and elucidate their antioxidant effect using in vitro and in vivo models of cisplatin-induced acute renal failure. An enriched mixture of ginsenosides Rk3 and Rh4 (KG-KH; 49.3% and 43.1%, respectively) was purified from sun ginseng (heat processed Panax ginseng). Cytotoxicity was induced by treatment of 20μM cisplatin to LLC-PK1 cells and rat model of acute renal failure was generated by single intraperitoneal injection of 5 mg/kg cisplatin. Protective effects were assessed by determining cell viability, reactive oxygen species generation, blood urea nitrogen, serum creatinine, antioxidant enzyme activity, and histopathological examination. The in vitro assay demonstrated that KG-KH (50 μg/mL) significantly increased cell viability (4.6-fold), superoxide dismutase activity (2.8-fold), and glutathione reductase activity (1.5-fold), but reduced reactive oxygen species generation (56%) compared to cisplatin control cells. KG-KH (6 mg/kg, per os) also significantly inhibited renal edema (87% kidney index) and dysfunction (71.4% blood urea nitrogen, 67.4% creatinine) compared to cisplatin control rats. Of note, KG-KH significantly recovered the kidney levels of catalase (1.2-fold) and superoxide dismutase (1.5-fold). Considering the oxidative injury as an early trigger of cisplatin nephrotoxicity, our findings suggest that ginsenosides Rk3 and Rh4 protect the kidney from cisplatin-induced oxidative injury and help to recover renal function by restoring intrinsic antioxidant defenses.